The Laughing Girl - Chambers, Robert W. (Robert William), 1865-1933; Hutt, Henry, 1875-1950 (Salt Lake City, UT : Project Gutenberg, 2016)
"The Laughing Girl" by Robert W. Chambers is a novel written in the early 20th century. The story introduces Michael O'Ryan, who has unexpectedly inherited a property in Switzerland, complete with a deserted chalet and a curious red-headed maid named Thusis. The novel explores themes of identity, absurdity, and the complexities of personal relationships against the backdrop of a war-torn world. At the start of the book, O'Ryan arrives at his new property, only to find it devoid of life except for the maid, Thusis, who surprises him with her unexpected beauty and charm. As the narrative unfolds, O'Ryan grapples with the absurdity of his inheritance and the insistence of local authorities that he must operate the property as a hotel. He is accompanied by his friend Smith, who speculates about the nature of the maid and her resemblance to a photograph of "The Laughing Girl" that O'Ryan treasures. The dynamics between the characters set the stage for a humorous and profound exploration of societal expectations, self-identity, and the allure of the unknown. (This is an automatically generated summary.)
Release date is 2016-10-10
Produced by Al Haines
Keywords: Love stories; Switzerland -- Fiction; Hotels -- Fiction; World War, 1914-1918 -- Switzerland -- Fiction